INFORMATION TECHNOLOGIES OF BUSINESS ANALYSIS IN THE MANAGEMENT AND DESIGN OF ACTIVITIES OF UKRAINIAN COMPANIES - KOVALENKO, Nadiia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the effectiveness and promising possibilities of using information technologies in the management and design of the activities of Ukrainian companies. It was established that the main task of business analysis is the collection and substantiation of information for making business decisions with the aim of improving management and project activities. Concretely, business analytics is considered as a process of gathering and forming an information base of indicators by using methods of information gathering and processing, risk assessment, modeling and forecasting. The types of software that will allow automating the management and project process of the company by forming an information database are detailed. It has been proven that Ukrainian companies have a significant gap in analytical activities, because in Ukraine, the profession classifier does not provide for the position of business analysts and their certification procedure. Accordingly, the perspective of the formation of business analytical data is the use of information technologies with software that automates the process of processing information and improving the management and project activities of Ukrainian companies.
Keywords: business analysis; information technologies; analytical support; design and management activities